Growth and Banking Structure in a Partially Dollarized Economy - Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2007)
This article illustrates how the industrial organization of a banking system affects economic growth in a partially dollarized economy. I study a model where banking competition has some potentially good and some potentially bad effects for growth. I analyze how important they are quatitatively and, surprisingly, they do not seem to matter much. The main reason for this is that while competition leads banks to offer consumers a "better deal" on their deposits, this does not lead to a large increase in the savings rate. The effect depends on the main structural parameter values of the economy. In particular, if there is a high demand for liquidity insurance. I calibrate the model for the Bolivian economy and show that the growth rates under both systems are not significantly different.
Keywords: D50; F31; G21; L10; 330; General equilibrium and growth; Dollarization; Banking; Industrial Organization